The artful read-aloud : 10 principles to inspire, engage, and transform learning. - Bellingham, Rebecca (Portsmouth : Heinemann USA Imprint, 2019)
It's no secret that reading aloud to children every single day is one of the most important things any teacher, parent, or grown up can do to help children become better readers, thinkers, and frankly, better human beings. There are many resources available?scores of books, articles, web sites, videos, podcasts, and more that highlight the research on why reading aloud to kids is so vital, how to incorporate it into the day, and lists of texts to choose from for each grade level. The Artful Read-Aloud is a user-friendly guide that builds a bridge between the artistic world and the classroom, providing a deeper dive into the artistry of reading aloud. Rebecca Bellingham draws on her experience as a performer, teaching artist, classroom teacher, and literacy coach to make explicit connections between the arts and reading aloud, providing dozens of easy moves teachers can make that can enhance, elevate, and deepen the impact of interactive read-alouds. Each chapter focuses on a specific guiding principle that is drawn from the arts and is meant to spark engagement, provoke inquiry, and inspire deep thinking. She includes practical tips for how to bring each principle to life in the classroom, including: how to embody the text by making small shifts with your body and voice to bring the words to life, helping kids envision different characters and their actions more completely learning when to slow down, pause, and read in an deliberate and careful way to give kids time to think, feel, process, and connect when and how to create opportunities for talk, giving kids the space to ask questions and reflect on what they notice, wonder, and predict how to give kids a chance to move around as they try on characters, recreate scenes, learn about new concepts, and live inside the book prioritizing read alouds that give students practice listening to and learning from diverse voices while creating space for meaningful conversation about important issues relating to injustice, identity, inequality, and more ways to be intentional in your choices, from matching books to the students in front of you to choosing passages that support instructional goals and teaching points. Reading aloud to your students supports a balanced, rigorous, and joyful literacy curriculum that not only feeds the souls and minds of your students but your own as well. Dip into The Artful Read-Aloud and see what's possible inside your daily read-alouds. By learning to make simple moves that model what real reading looks and sounds like you can help your students become the kind of readers all of us hope they will become: engaged, thoughtful, lifelong ones.
Abridged.
Requires OverDrive Listen (file size: N/A KB) or OverDrive app (file size: 145548 KB).
Professional.
SORA audiobook.
Keywords: Nonfiction; Education; Electronic books; Oral reading; SORA Audiobooks